Reviewing the Reviewers: (Re)Translations and the Literary Press - Wardle, Mary (Vertimo studijos, 2020)
Within the wider context of (re)translation and reception, this paper outlines a model for assessing how literary review publications address (re)translated works and whether there has been any discernable evolution in their approach over the period during which Translation Studies has emerged and consolidated itself as an academic discipline: the corpus comprises all issues over three separate years (1980, 2000 and 2018) of two international, English-language literary reviews (The New York Review of Books and London Review of Books). The analysis covers all reviews of works of literature translated from any language into English, both for the first time and retranslations, assessing whether there is any observable diachronic change over the time period in question. Although the scope of the material under inspection is limited, this study outlines the methodology developed for analyzing the manner in which reviews address translated texts and, more specifically, retranslations: this methodology, which involves classifying the corpus according to a taxonomy of features typical of the genre, is applicable to wider investigations across different languages, text types, time spans, platforms. Issues examined include how the reviewers assess the quality of the (re)translations; how texts are quoted; the significance of paratextual elements; the figure of the reviewer; whether retranslation is highlighted and/or reviewed differently to first translations. Future applications of the model are also considered.
Keywords: translation reviews; literary press; retranslation; model for review analysis